Quality Management System for Stable Product and Customer Reliability: Sistem Manajemen Mutu untuk Kualitas Produk yang Stabil dan Keandalan Pelanggan - Ashurova Zarina Olimjonovna (Academia Open, 2025)
General Background: In the context of globalization, the construction industry plays a critical role in economic growth and social stability, with building material enterprises serving as its central link. Specific Background: In Uzbekistan, rapid infrastructural development has increased the demand not only for higher production volumes but also for building materials that meet international quality standards. Knowledge Gap: Despite the global relevance of quality management systems (QMS), many local enterprises still approach quality reactively rather than strategically, limiting competitiveness and sustainability. Aims: This study investigates the effectiveness of implementing QMS, particularly ISO 9001:2015, in enterprises producing building materials, focusing on its role in improving product quality and organizational performance. Results: A comparative analysis of 20 enterprises revealed that those applying ISO 9001 achieved significantly lower defect rates (3% vs. 11%), higher customer satisfaction (92% vs. 71%), and greater production stability (87% vs. 65%). Novelty: By critically integrating international theories with local practice, the study highlights the importance of process standardization, employee competence, and continuous improvement as key drivers of quality. Implications: The findings demonstrate that adopting QMS should move beyond certification toward full integration into corporate strategy, serving as a catalyst for competitiveness, sustainable growth, and industry-wide modernization.Highlight : Standardization of processes is the main factor influencing product quality. ISO 9001:2015 improves customer satisfaction and production stability. Quality management must involve employees and be applied continuously. Keywords : Quality Management, Building Materials, ISO 9001:2015, Product Quality, Corporate Quality Culture